(untitled) - Heer, Friedrich (Cleveland, 1953)
With the unifying theme of the Enlightenment tradition and two introductory chapters on the evolution of Western intellectual tradition, the text provides students with the framework and background they need to understand the history of modern European thought. The nineteenth and the first half of the twentieth centuries are examined in relation to the Enlightenment.
Keywords: Philosophy,Religious thought,Triết học,Triết học,Tư tưởng tôn giáo; History,Lịch sử,Lịch sử; Europe,Châu Âu